Space up/ Vanessa Sebastian, Fazlin Awaludin and Aimi Zahirah Zulkarnian - Sebastian, Vanessa; Awaludin, Fazlin; Zulkarnian, Aimi Zahirah (2023)
SPACE UP is a ground-breaking interactive kit that seamlessly merges interior design principles, offering a handson exploration of creative space planning and aesthetics. This kit empowers designers to confidently embark on the journey of transforming spaces with their distinctive styles while emphasizing the crucial role of sensory-motor integration and experiential learning in shaping cognitive development. This product underscores the paramount importance of integrating sensory-rich, motor-engaging learning strategies in early education to cultivate holistic cognitive development. Notably, the SPACE UP kit introduces novel approach featuring modular design components, allowing users to blend and match elements for crafting personalized furniture and decor pieces. This design innovation promotes creativity and adaptability in the field of design. Furthermore, SPACE UP introduces Interactive Design Boards, a departure from traditional static mood boards. These interactive boards enable users to dynamically arrange and rearrange design elements, facilitating a flexible and dynamic design process. This approach underscores the significance of incorporating sensory-rich, motor-engaging learning strategies, providing youn designers with a comprehensive and enriching educational experience. In conclusion, SPACE UP illuminates the profound impact of hands-on learning on cognitive development within the realm of design studio education, presenting an exciting avenue for design innovation competition